POMT1 is essential for protein O-mannosylation in mammals - Lommel, Mark; Strahl, Sabine (Functional glycomics, 2010)
Over the past decade it has emerged that O-mannosyl glycans are not restricted to yeast and fungi but are also present in higher eukaryotes up to humans. In mammals, the protein O-mannosyltransferases POMT1 and POMT2 act as a heteromeric complex to initiate O-mannosylation in the endoplasmic reticulum. In humans, mutations in POMT1 and POMT2 result in hypoglycosylation of α-dystroglycan (α-DG) thereby abolishing its binding to extracellular matrix ligands such as laminin. As a consequence, POMT mutations cause a heterogeneous group of severe recessive congenital muscular dystrophies in humans. However, little is known about the function of O-mannosyl glycans in mammals apart from its crucial role for the ligand binding abilities of α-DG. In this chapter we discuss the methods used to analyze the expression of Pomt1 in adult mouse organs and during embryo development. Further, we describe the generation and immunohistochemical analysis of Pomt1 knockout mice.
Gesehen am 24.05.2017